Volitional Determinants and Age-related Decline in Fecundability: A General Population Prospective Cohort Study in Denmark - Rothman, Kenneth J. (2013)
OBJECTIVE: To quantify the natural decline in fecundability by age and assess the effect of selected volitional factors. DESIGN: Prospective cohort study of women attempting conception. SETTING: General population cohort of Danish women aged 20–40 years. PARTICIPANTS: 2,820 women without infertility, trying to conceive for less than 3 cycles at study entry. INTERVENTION: none. OUTCOME MEASURE: fecundability. RESULTS: Age had little effect on fecundability except for women 35–40 yrs, for whom it was 0.77 relative to women aged 20–24. Male age showed a similar but smaller drop, declining to 0.95 for men aged 35–39. The effect of age differed for parous and nulliparous women, with the latter experiencing much stronger age-related declines relative to fecundability at age 20. Frequency of intercourse, use of nonhormonal birth control as the last method, and timing of intercourse each had small effects on fecundability. Women who were in the high-fecundability categories for all three of these volitional factors had an estimated probability of conceiving of 88% (95% CI: 83%–93%). Unlike age, these factors represent individual choices that together can offset some of the age-related decline in fecundability. CONCLUSION: Fecundability peaks around age 30, slightly earlier for nulliparous than for parous women, and then declines. The decline with age is more modest for males. Couples will experience a compounded effect of their separate age-related declines. At age 40, a couple’s fecundability would be approximately half of what it is at age 30, but some of this decline can be counteracted by volitional factors affecting conception.